Practical studies in Revelation ; v. 1 - Epp, Theodore Herman, 1907-1985 (Lincoln, NE Back to the Bible Broadcast, 1969)
Contents v. 2 : chapters 1-3 : Christ and the church
Donated by John Dickson, Dec. 2002.
Keywords: Bible. N.T. Revelation I-III -- commentaries